Eyewitness susceptibility to co-witness misinformation is influenced by co-witness confidence and own self-confidence. Issue 4 (21st April 2017) - Thorley, Craig; Kumar, Devvarta
ABSTRACT: If an eyewitness is exposed to a co-witness statement that incorrectly blames an innocent bystander for a crime, the eyewitness can be influenced by this statement and also blame the innocent bystander for the crime. This effect is known as blame conformity. In two studies, we examined whether or not this effect is influenced by the degree of confidence a co-witness expresses in her incorrect statement (Study 1) and an eyewitness's own level of self-confidence (Study 2). Participant eyewitnesses first watched a crime video featuring a perpetrator and an innocent bystander, then read a co-witness statement about the crime that either correctly blamed the perpetrator, incorrectly blamed the innocent bystander, or blamed nobody (a control condition). They were then asked who committed the crime. In Study 1, participants who read an incorrect statement were at increased risk of engaging in blame conformity when the co-witness expressed a high level of confidence, compared to a low level of confidence, in the accuracy of her statement. In Study 2, participants who were lowest in self-confidence were at increased risk of engaging in blame conformity. The theoretical underpinnings of these effects are considered.